A systematic review and network meta-analysis of phase III randomised controlled trials for adjuvant therapy following resection of pancreatic ductal adenocarcinoma (PDAC). Issue 5 (May 2020) - Kamarajah, Sivesh K.; Bundred, James R.; Alrawashdeh, Wasfi; Manas, Derek; White, Steven A.
Abstract: Background: Several randomised controlled trials (RCTs) have reported various systemic adjuvant therapy regimens following resection of pancreatic ductal adenocarcinoma (PDAC). The most commonly applied include modified FOLFRINOX (mFFX), Gemcitabine/Capecitabine (GemCap) and S1, usually compared to gemcitabine (Gem) alone. However, many of these regimens have not been directly compared in RCTs. This network meta-analysis aims to characterise the impact of adjuvant therapies on overall and disease-free survival in patients having resection of PDAC. Methods: A systematic review was conducted using MEDLINE, EMBASE, Cochrane Central and American Society of Clinical Oncology (ASCO) abstracts to identify published phase III RCTs articles up to 9th May 2019 that examined adjuvant systemic therapy in resected pancreatic cancer. Data including study characteristics and outcomes including overall survival (OS) and disease-free survival (DFS) were extracted. Indirect comparisons of all regimens were simultaneously compared using random-effects network meta-analyses (NMA) which maintains randomisation within trials. Results: Twelve phase III RCTs involving 4947 patients and nine different regimens (5-Flourouracil/Folinic acid (5-FU/FA), Gemcitabine, Gemcitabine/Erlotinib (GemErl), GemCap), mFFX, S1, chemoradiotherapy (CRT), CRT with either 5-FU or Gemcitabine) were identified. S1 was ranked best for overall and disease-free survival followed by mFFX. Whilst there were no significant difference between S1 and mFFX for overall survival (mean difference: 1.6 months, p = 0.8), S1 had significantly longer disease-free survival than mFFX (mean difference: 2.8 months, p < 0.001). Furthermore, S1 was ranked best for lowest overall and haematological grade 3/4 toxicities. Conclusion: This network meta-analysis demonstrates that chemotherapy with S1 or mFFX is superior to GemCap for adjuvant treatment for PDAC, improves survival after surgical resection and should be considered as reasonable standard treatment options in the adjuvant setting and as control arm for future adjuvant clinical trials.